Bed level changes in the surf zone during post-storm beach recovery - Hu, Pengpeng; Li, Zhiqiang; Zeng, Chunhua; Zhu, Daoheng; Liu, Run; Su, Qianxin; Tang, Jieping; Zhu, Yamin (Frontiers in Marine Science, 2023)
The study of post-storm beach recovery is important for economic development and the protection of life in coastal areas. In this study, field observations were conducted for 21 days in the surf zone of Dongdao Beach, Hailing Island, China, after tropical storm “Cempaka”. Data on depth, wave, Eulerian velocity, sediment, three-dimensional topography of the beach, and high-frequency variations in bed-level elevation were collected. The results showed that the beach experienced medium- to low- to medium-energy waves during field observations and covered two complete astronomical tide cycles. Contrary to the effect of wave energy conditions on beaches under normal wave conditions, a higher wave energy during beach recovery can promote silting and accelerate beach recovery. Tidal water level is an important factor affecting beach restoration, and a smaller tidal range is conducive to beach accretion. In a mixed semidiurnal tide, beach erosion and accretion occurred in the “highest tide” and “sub-highest tide” tidal cycles, respectively, and the combined effect of the two affected the change in the bed level in a mixed semidiurnal tide. After the storm, the hydrodynamic forcing mechanism and self-organization process of the sand bar jointly drove the formation of the topography of the bar channel in the surf zone. After the storm stopped, the spectral energy in free surface elevation was mainly distributed in the very low frequency and decayed rapidly at the infragravity band. The very low-frequency pulsation of the surf zone during recovery is a prominent feature of bed-level elevation, depth, and velocity. This study provides a good case for the study of hydrodynamic and bed level changes in the post-storm surf zone, as well as a reference for future studies of the intrinsic mechanisms post-storm beach recovery processes around the world.